Analisis Sentimen Konsumen Terhadap Pertumbuhan Zakat: Studi Kasus Lembaga Amil Zakat Nasional Tahun 2018-2022 - Apriyadi, Pidi; Cupian, Cupian (ITB AAS INDONESIA Surakarta, 2024)
Studies on the correlation between consumer sentiment, as measured using the consumer confidence index, and zakat growth are limited. Studies related to this topic are important because the consumer confidence index, as an indicator of consumer sentiment, can reflect people's behavior in paying zakat. This study explores the relationship between the consumer confidence index and zakat growth in Indonesia in the 2018-2022 period. Data on zakat is obtained from the financial statements of national zakat institutions, while data on the consumer confidence index is obtained from Bank Indonesia. Through the Arellano-Bover/Blundell Bond two-step GMM system approach, the study concluded that the consumer confidence index did not have a significant impact on zakat growth. This finding is a contribution in understanding why the potential of zakat in Indonesia has not been optimized, in line with the existing literature. The research also offers an update in the use of consumer sentiment indicators.